Embedded System for Real-Time Digital Processing of Medical Ultrasound Doppler Signals. (21st May 2008) - Ricci Ricci, S. S.; Dallai Dallai, A. A.; Boni Boni, E. E.; Bassi Bassi, L. L.; Guidi Guidi, F. F.; Cellai Cellai, A. A.; Tortoli Tortoli, P. P.
Abstract : Ultrasound (US) Doppler systems are routinely used for the diagnosis of cardiovascular diseases. Depending on the application, either single tone bursts or more complex waveforms are periodically transmitted throughout a piezoelectric transducer towards the region of interest. Extraction of Doppler information from echoes backscattered from moving blood cells typically involves coherent demodulation and matched filtering of the received signal, followed by a suitable processing module. In this paper, we present an embedded Doppler US system which has been designed as open research platform, programmable according to a variety of strategies in both transmission and reception. By suitably sharing the processing tasks between a state-of-the-art FGPA and a DSP, the system can be used in several medical US applications. As reference examples, the detection of microemboli in cerebral circulation and the measurement of wall _distension_ in carotid arteries are finally presented.